Bacteriophages as indicators of faecal pollution and enteric virus removal. (5th June 2017) - McMinn, B.R.; Ashbolt, N.J.; Korajkic, A.
Abstract: Bacteriophages are an attractive alternative to faecal indicator bacteria (FIB), particularly as surrogates of enteric virus fate and transport, due to their closer morphological and biological properties. Based on a review of published data, we summarize densities of coliphages (F+ and somatic), Bacteroides spp. and enterococci bacteriophages (phages) in individual human waste, raw wastewater, ambient fresh and marine waters and removal through wastewater treatment processes utilizing traditional treatments. We also provide comparisons with FIB and enteric viruses whenever possible. Lastly, we examine fate and transport characteristics in the aquatic environment and provide an overview of the environmental factors affecting their survival. In summary, concentrations of bacteriophages in various sources were consistently lower than FIB, but more reflective of infectious enteric virus levels. Overall, our investigation indicates that bacteriophages may be adequate viral surrogates, especially in built systems, such as wastewater treatment plants. Significance and Impact of the Study: Bacteriophage are alternative fecal indicators that may be better surrogates for viral pathogens than fecal indicator bacteria (FIB). This report offers a summary of the existing literature concerning the utility of bacteriophage as indicators of viral presence (fecal sources and surface waters) and persistence (in built infrastructure and aquatic environments). Our findings indicate that bacteriophage levels in all matrices examined are consistently lower than FIB, but similar to viral pathogens. Furthermore, in built infrastructure (e.g. wastewater treatment systems) bacteriophage closely mimic viral pathogen persistence suggesting they may be adequate sentinels of enteric virus removal. Abstract : Significance and Impact of the Study: Bacteriophage are alternative fecal indicators that may be better surrogates for viral pathogens than fecal indicator bacteria (FIB). This report offers a summary of the existing literature concerning the utility of bacteriophage as indicators of viral presence (fecal sources and surface waters) and persistence (in built infrastructure and aquatic environments). Our findings indicate that bacteriophage levels in all matrices examined are consistently lower than FIB, but similar to viral pathogens. Furthermore, in built infrastructure (e.g. wastewater treatment systems) bacteriophage closely mimic viral pathogen persistence suggesting they may be adequate sentinels of enteric virus removal.